IMAGINING DARKNETS: PRIVACY AS COMMODITY AESTHETICS - Hunsinger, Jeremy (AoIR Selected Papers of Internet Research, 2015)
As a field of distributed subjectivity, consumption is one mode through which we co- construct ourselves and our relation to things. Darknets and their users are clearly participating in reconstituting field of consumption, as is the internet in which darknets exist. Within consumption we labor to represent ourselves in relation to our material relations(Baudrillard, 1981) (Baudrillard, 1998). This paper argues that darknet users examples of both the de-massification of internet audiences and the re-constitution of a mass consumer identity centered on the commodity aesthetics of darknets(Haug, 1986). Specifically, I demonstrate that privacy on darknets is not so much a matter of reality but is a matter of a perceived commodity aesthetic by their subjective audience. Our consumption and our co-construction of the relations of our subjective approaches to commodity aesthetics is both the identification and alienation of the reflexive awareness of the subject’s desires/needs. Within darknets these desires/needs extend through our simplest curiosities, to political organizing, to representations of illicit activities, to the activities themselves. The alienation and identification of desires functions much like the creation of the identity qua the quasi-object that is produced is always partly the user’s alienated identity (Gehl, 2014; Herman, 2013; Latour, 1993). This process produces the capacity to realize the values in the darknets as capital itself, including the values found in the relationship to the materiality of capital presented therein. Given the proclivities of the representations of constituted on darknets, this proposal examines how users create and recreate the darknet, both as a capital materiality and as an capital idea. Fundamentally, my argument resists the idea of criminality and exceptionalism found in popular press understandings of darknets, in favor of the argument that although the criminal element does exist, the broader nature of capital in darknets is about knowledge, information provision, and economic value creation. In short, I argue that the representation of material and non-material capital on darknets creates a wild zone of consumption allowing the subject to be reconstituted with the awareness of an extended horizon (Luke, 1995);(O’Tuathail, 1994)